Daratumumab monotherapy in patients with treatment-refractory multiple myeloma (SIRIUS): an open-label, randomised, phase 2 trial. Issue 10027 (9th April 2016) - Lonial, Sagar; Weiss, Brendan M; Usmani, Saad Z; Singhal, Seema; Chari, Ajai; Bahlis, Nizar J; Belch, Andrew; Krishnan, Amrita; Vescio, Robert A; Mateos, Maria Victoria; Mazumder, Amitabha; Orlowski, Robert Z; et al.
Summary: Background: New treatment options are needed for patients with multiple myeloma that is refractory to proteasome inhibitors and immunomodulatory drugs. We assessed daratumumab, a novel CD38-targeted monoclonal antibody, in patients with refractory multiple myeloma. Methods: In this open-label, multicentre, phase 2 trial done in Canada, Spain, and the USA, patients (age ≥18 years) with multiple myeloma who were previously treated with at least three lines of therapy (including proteasome inhibitors and immunomodulatory drugs), or were refractory to both proteasome inhibitors and immunomodulatory drugs, were randomly allocated in a 1:1 ratio to receive intravenous daratumumab 8 mg/kg or 16 mg/kg in part 1 stage 1 of the study, to decide the dose for further assessment in part 2. Patients received 8 mg/kg every 4 weeks, or 16 mg/kg per week for 8 weeks (cycles 1 and 2), then every 2 weeks for 16 weeks (cycles 3–6), and then every 4 weeks thereafter (cycle 7 and higher). The allocation schedule was computer-generated and randomisation, with permuted blocks, was done centrally with an interactive web response system. In part 1 stage 2 and part 2, patients received 16 mg/kg dosed as in part 1 stage 1. The primary endpoint was overall response rate (partial response [PR] + very good PR + complete response [CR] + stringent CR). All patients who received at least one dose of daratumumab were included in the analysis. The trial is registered with ClinicalTrials.gov, number NCT01985126 . Findings: The study is ongoing. In part 1 stage 1 of the study, 18 patients were randomly allocated to the 8 mg/kg group and 16 to the 16 mg/kg group. Findings are reported for the 106 patients who received daratumumab 16 mg/kg in parts 1 and 2. Patients received a median of five previous lines of therapy (range 2–14). 85 (80%) patients had previously received autologous stem cell transplantation, 101 (95%) were refractory to the most recent proteasome inhibitors and immunomodulatory drugs used, and 103 (97%) were refractory to the last line of therapy. Overall responses were noted in 31 patients (29·2%, 95% CI 20·8–38·9)—three (2·8%, 0·6–8·0) had a stringent CR, ten (9·4%, 4·6–16·7) had a very good PR, and 18 (17·0%, 10·4–25·5) had a PR. The median time to first response was 1·0 month (range 0·9–5·6). Median duration of response was 7·4 months (95% CI 5·5–not estimable) and progression-free survival was 3·7 months (95% CI 2·8–4·6). The 12-month overall survival was 64·8% (95% CI 51·2–75·5) and, at a subsequent cutoff, median overall survival was 17·5 months (95% CI 13·7–not estimable). Daratumumab was well tolerated; fatigue (42 [40%] patients) and anaemia (35 [33%]) of any grade were the most common adverse events. No drug-related adverse events led to treatment discontinuation. Interpretation: Daratumumab monotherapy showed encouraging efficacy in heavily pretreated and refractory patients with multiple myeloma, with a favourable safety profile in this population of patients. Funding: Janssen Research & Development.